Social support against suicide in burn survivors: A vital but overlooked protective factor - Akbar Zare-Kaseb; Amir Mohammad Beigee; Amin Doustahadi; Maryam Shahabi; Mohammad Javad Ghazanfari (Journal of Nursing Reports in Clinical Practice)
N/A